Countering Fake BSY Noni Black Hair Magic in Malaysia (Global Business Management Review (GBMR), 2019)
Choong Li Li is the sole owner of LLC Health Care Global company in Malaysia. Choong Li Li started the company in 2012 using her personal savings of RM30 000. She is assisted by four staff. In 2014, BSY Group China appointed LLC Healthcare Global as the sole distributor for BSY Noni Black Hair Magic in Malaysia. BSY which stands for Beautiful, Salubrious and Young has quite a big market share in the hair dye market in Malaysia. Unfortunately, the product was quickly copied by competitors using the same brand name BSY Noni Black Hair Magic as well as same BSY green colour packaging. The counterfeit product was priced much lower than the genuine BSY Noni Black Hair Magic product. Consumers found it difficult to differentiate the genuine from the fake product.Because of the rampant and countrywide sale of counterfeit BSY Noni Black Hair Magic product as well competition from other brands, LLC Healthcare Global found it very challenging to maintain the BSY Noni Black Hair Magic market share in Malaysia. On top of that, LLC Healthcare Global has to meet its annual sales target of RM 1 million. Meeting the sales target was very important for her to maintain her BSY Noni Black Hair Magic sole distribution right in Malaysia. Choong Li Li has to find ways to meet her sales quota for the year as well as figure out long term strategies to overcome the ever present fake BSY Noni Black Hair Magic that flooded the hair dye market.